Monetary policy in the aftermath of currency crisis: the case of Asia - Ilan Goldfajn; Taimur Baig (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 1999)
This paper evaluates monetary policy and its relationship with the exchange rate in the five Asian crisis countries. The findings are compared to previous currency crises in recent history. The paper finds that there is no evidence of overly tight monetary policy in the Asian crisis countries in 1997 and early 1998. There is also no evidence that high interest rates led to weaker exchange rates. The usual trade-off between inflation and output when raising interest rates suggested the need for a softer monetary policy in the crisis countries to combat recession. However, in some countries, corporate balance sheet considerations suggested the need to reverse overly depreciated currencies through firmer monetary policy.
Keywords: E44; E63; 330